Development of a colloidal gold-based immunochromatographic strip for rapid detection of Areca palm velarivirus 1 - Lu, Jie; He, Weifan; Liu, Yuxing; Li, Shiqi; Huang, Xi; Wang, Hongxing; Cao, Xianmei (Frontiers in Microbiology, 2025)
BackgroundAreca palm velarivirus 1 (APV1), the causal agent of betel palm yellow leaf disease (YLD), has caused significant yield losses and decreased product quality of betel nuts, posing a serious economic threat to local farmers. There is an urgent need for a convenient and reliable method for the rapid detection and surveillance of APV1.MethodsThe Capsid protein (CP) of APV1 was expressed in Escherichia coli and purified as antigen to immunize BALB/c mice. Two specific monoclonal antibodies (MAbs), APV1CP-1 and APV1CP-10, were generated through the hybridoma technique. APV1CP-1 was conjugated with colloidal gold served as detection reagent, while APV1CP-10 was coated onto a porous nitrocellulose membrane to act as the detection line. Goat anti-mouse IgG was used as the control line. These components were then assembled into a colloidal gold immunochromatographic strip (CGICS) for effective detection of APV1.ResultsThe MAbs APV1CP-1 and APV1CP-10 were successfully obtained with titers exceeding 1:102,400. Colloidal gold particles used in the assay had an approximate diameter of 30–40 nm, and exhibited a surface plasmon resonance peak around 530 nm. The CGICS allowed for the detection of APV1 by applying infected sap to the test strip, with results visible within 5–10 min. The test showed no cross-reactivity with other viruses tested, and the visual detection limit for APV1 was established at a 100-fold dilutions of APV1-infected leaf samples.ConclusionThe monoclonal antibody-based colloidal gold immunochromatographic strip developed in this study demonstrates significant convenience, rapidity, and reliability for APV1 detection. These advancements are anticipated to facilitate rapid diagnosis and surveillance of APV1 in field settings.